Identifikasi Potensi dan Karakterisasi Kandungan Mineral dan Unsur Penyusun pada Pasir di Kelurahan Sei Gohong - Virgiyanti, Lisa; Sukmawatie, Neny; Indrajaya, Fahrul (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this research was aims to find out minerals percentage in the sand sample at Sei Gohong villages and to identify the potential and characterization of mineral content and its elements, which validated by laboratory analysis. The sample tested was the sand from the research location at Sei Gohong Village, Central Kalimantan. Based on these objectives, it is necessary to develop an identification of the characterisation and potential of sand deposits based on differences in the types of mineral deposits. The identification process was carried out using X-Ray Diffraction (XRD) analysis and X-Ray Flourescence (XRF) analysis. The results of research on 4 (four) sand samples in Sei Gohong Village show that the percentage of dominant mineral content in sand in Sei Gohong Village is Quartz (SiO2) with an average of 97,72% followed by other mineral constituents such as Calcium Oxide (CaO), Rutile (TiO2), Shcherbinaite (V2O5), Eskolaite (Cr2O3), Hematite (Fe2O3), Manganosite (MnO), Bunsenite (NiO), Tenorite (CuO), Zinc (ZnO) and Rhenium (Re2O7). The results of XRD analysis show that the dominant compound found in sand samples in Sei Gohong Village is Quartz (SiO2) Keywords: SiO2,; X-Ray Difraction (XRD); X-Ray Flourescence (XRF)